(untitled) - Ferris, Timothy (New York, 1983)
Hailed by the critics as a classic modern science writing, The Red Limit was awarded the American Institute of Physics Prize
Keywords: Cosmology,Vũ trụ học,Expanding universe,Khám phá vũ trụ